Safety and Efficiency of Biomimetic Nanohydroxyapatite/Polyamide 66 Composite in Rabbits and Primary Use in Anterior Cervical Discectomy and Fusion - Hui Xu; Yan Wang; Xiaojing Su; Xuelian Zhang; Xuesong Zhang (International Journal of Polymer Science)
This study was conducted to validate the safety and efficiency of biomimetic nanohydroxyapatite/polyamide 66 (n-HA/PA66) composite in animal model (rabbit) and report its application in anterior cervical discectomy and fusion (ACDF) for 4, 12, and 24 weeks. N-HA/PA66 composite was implanted into one-side hind femur defects and the control defects were kept empty as blank controls. A combination of macroscopic and histomorphometric studies was performed up to 24 weeks postoperatively and compared with normal healing. 60 cervical spondylosis myelopathy and radiculopathy patients who were subjected to ACDF using n-HA/PA66 and PEEK cage were involved in this study with six-month minimum follow-up. Their radiographic (cage subsidence, fusion status, and segmental sagittal alignment (SSA)) and clinical (VAS and JOA scales) data before surgery and at each follow-up were recorded and compared. Nanohydroxyapatite/polyamide 66 composite is safe and effective in animal experiment and ACDF.